Exercise can rescue recognition memory impairment in a model with reduced adult hippocampal neurogenesis - Lafenetre, Pauline; Leske, Oliver; Ma-Högemeie, Zhanlu; Haghikia, Aiden; Bichler, Zoe; Wahle, Petra; Heumann, Rolf (Frontiers in Behavioral Neuroscience, 2010)
Running is a potent stimulator of cell proliferation in the adult dentate gyrus and these newly generated hippocampal neurons seem to be implicated in memory functions. Here we have used a mouse model expressing activated Ras under the direction of the neuronal Synapsin I promoter (named synRas mice). These mice develop down-regulated proliferation of adult hippocampal precursor cells and show decreased short-term recognition memory performances. Voluntary physical activity reversed the genetically blocked generation of hippocampal proliferating cells and enhanced the dendritic arborisation of the resulting doublecortin newly generated neurons. Moreover, running improved novelty recognition in both wild type and synRas littermates, compensating their memory deficits. Brain-derived neurotrophic factor (BDNF) has been proposed to be a potential mediator of physical exercise acting in the hippocampus on dentate neurons and their precursors. This was confirmed here by the identification of doublecortin-immunoreactive cells expressing TrkB BDNF receptor. While no difference in BDNF levels were detected in basal conditions between the synRas mice and their wild type littermates, running was associated with enhanced BDNF expression levels. Thus increased BDNF signalling is a candidate mechanism to explain the observed effects of running. Our studies demonstrate that voluntary physical activity has a robust beneficial effect even in mice with genetically restricted neurogenesis and cognition.